The word that swings (Palíndromo, 2024)
This article explores the use of words – elements of verbal language – in carnival parades at samba schools in Rio de Janeiro. Using the notion of ginga, given that these writings parade under turns, twirls and dances, a reflection is carried out mediated by several negative criticisms made regarding the use of these elements in carnival visuality. However, such criticisms treat the verbal dimension in these creations as something hierarchically smaller than the visual dimension. Due to this type of perspective on the presence of verbal elements in the parades of samba schools in Rio de Janeiro, we carried out a survey of several examples of this occurrence which, in our understanding, demonstrate the potential of verbal language in constituting the visuality of Carnival, as well as in increasing the meanings of different sambas plot.
Keywords: carnival; verbal language; samba plot; carnival visuality